空気電池用正極及びその製造方法 (2018)
PROBLEM TO BE SOLVED: To provide a positive electrode for air batteries which enables the materialization of a higher output of an air battery.SOLUTION: A positive electrode 10 for air batteries comprises a catalyst layer 11 and a liquid-tight gas-permeable layer 12 which are laminated together. The catalyst layer 11 is composed of a porous layer including: carbon particles 1; catalyst particles 2; a binder 3; and hydrophilic particles 4. The hydrophilic particles 4 in the catalyst layer 11 facilitates the infiltration of an electrolytic solution D, and the number of active points at three-phase interfaces of catalyst, oxygen have passed through the liquid-tight gas-permeable layer 12, and the electrolytic solution D is increased, whereby an air battery with a higher output can be materialized.